Faktor-Faktor yang Mempengaruhi Perilaku Merokok pada Remaja - Amelia Safitri; Mohammad Avicenna; Netty Hartati (‎‎‎TAZKIYA Journal of Psychology, 2013)
The present study investigated factors that influence smoking behavior among adolescents.Peer attachement, stress (increased workload, lack of academic performance and lower gradethat anticipated), parenting styles (authoritarian, authoritative, and permissive) werehypothesized influence adolescent involvement in smoking. A number of 249 students thatcame from SMP Darussalam Jagakarsa South Jakarta and actively smoking were recruitedusing non-probably sampling. Confirmatory Factor Analysis and Multiple RegressionAnalysis were carried out to evaluate validity of the scales and answer of the researchquiestions by using SPSS and LISREL 8.70 programs. The results found that peerattachment , stress, and parenting styles significantly influence smoking behavior amongadolescents (p < 0.05), (F=39.676, df=7) and R2=53.5%. However, analysis based on eachdimension only four dimensions significantly influence smoking behavior, namely peerattachment , lack of academic performance, increased workload, and authoritative parenting(p-value < 0.05). This study suggested to conduct more extensive research to investigate theinfluence of stress especially getting lower grade that anticipated; and authoritarian andpermissive parenting styles on smoking behavior among adolescents. Moreover, the studysuggested to develop scale that suitable with indonesian culture, as well as to recruit morefemale adolescent smokers.